Mosquito net use and malaria falciparum infection in Puerto Princesa City, Palawan Province, Philippines - Roosihermiatie, Betty
A health facility-based unmatched case control study was conducted in the City Health Office, the Malaria Control Office and the Palawan Provincial Hospital in Puerto Princesa City, Palawan Province during the period of October-December 1994 to determine the association between regular use of mosquito-net at night and malaria falciparum infection.One hundred fifty cases and controles were included in this study. A majority of the study subjects were 26-45 years old, of low educational attainment and low income, lived in a temporary or dwelling type of house and in agricultural barangays at the outskirts city.The risk of having malaria falciparum infection for those who used mosquito-net regularly at night was only 25(OR=0, 25, 95CI : 0.15-0.42) compared to those who used mosquito-net irregularly. This association is statistically significant.The regularity of use of mosquito net itself protects the individuals from man-vector contact, considering that malaria vector bites at night. The protection offered was not affected by age, sex, type of house, income, pesent occurrence of malaria vector breeding places.This result may be used as a basis for the Malaria Control service to decrease malarial morbidity and mortality through the promotion of regular mosquito-net use at night.